"Doing death": Reflecting on the researcher's subjectivity and emotions. Issue 1 (2nd January 2017) - Visser, Renske C.
ABSTRACT: Given that death is a universal concept, the idea that a researcher must be objective when studying this topic is common place and problematic. Thus, this article adds to the literature by discussing the complexity of subjectivity within death studies. Three key elements of subjectivity form the basis of this discussion: (a) the researcher's cultural background, (b) the researcher's personal experiences, and (c) the emotional impact of research on the researcher. It is argued that transparency about the subjective nature of death studies research can be fruitful in understanding the research process before, during, and after fieldwork.